IMPROVING THE PROCESS OF USING NEW ADVANCED PEDAGOGICAL TECHNOLOGIES IN THE EDUCATION OF PRESCHOOL CHILDREN - G. Sh. Ibrahimova, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
this article will talk about the use of advanced pedagogical technologies in the education of preschool children, problems that May and may arise in the process of applying them to practice, tasks aimed at eliminating and preventing them.